Frequency optimization of laminated skewed open cylindrical shells - Topal Umut; Uzman Ümit (Science and Engineering of Composite Materials, 2011)
This paper deals with frequency optimization of symmetrically laminated skewed open cylindrical shells. The design objective is the maximization of the fundamental frequency and the design variable is the fiber orientations. The first-order shear deformation theory (FSDT) is used for the finite element solution of the shells. The modified feasible direction (MFD) method is used for the optimization routine. For this purpose, a program based on FORTRAN is used. Finally, the numerical analysis is carried out to investigate the effect of skew angles, length to radius ratios, subtended angle and boundary conditions on, the optimal designs and the results are compared.